The Application of Programmable Logic Controllers (PLC) in Vocational Education - Wisnu Budiarjo; Trisna Ardi Wiradinata; Rolan Siregar; Yendi Esye; Eva Novianti; Bagus Tri Mahardika; Atik Kurnianto (JEPTIRA, 2025)
This article outlines a systematic training program aimed at introducing and improving participants' comprehension of Programmable Logic Controllers (PLCs), a fundamental element in industrial automation systems. The training employed practical, hands-on workshops concentrating on fundamental PLC principles, hardware types, programming languages, and operational procedures. The participants were vocational school educators, students, and undergraduate engineering majors. The findings indicated substantial enhancements in the understanding and utilization of PLCs in automation activities, effectively connecting theoretical education with practical industry applications. The results further illustrate the efficacy of experiential learning in cultivating practical skills necessary for meeting the requirements of Industry 4.0 settings.